Linking individual‐level functional traits to tree growth in a subtropical forest. Issue 9 (September 2016) - Liu, Xiaojuan; Swenson, Nathan G.; Lin, Dunmei; Mi, Xiangcheng; Umaña, María Natalia; Schmid, Bernhard; Ma, Keping
Abstract: Forging strong links between traits and performance is essential for understanding and predicting community assembly and dynamics. Functional trait analyses of trees that have correlated single‐trait values with measures of performance such as growth and mortality have generally found weak relationships. A reason for these weak relationships is the failure to use individual‐level trait data while simultaneously putting that data into the context of the abiotic setting, neighborhood composition, and the remaining axes constituting the overall phenotype. Here, utilizing detailed growth and trait data for 59 species of trees in a subtropical forest, we demonstrate that the individual‐level functional trait values are strongly related to individual growth rates, and that the strength of these relationships critically depends on the context of that individual. We argue that our understanding of trait–performance relationships can be greatly improved with individual‐level data so long as that data is put into the proper context.